Applicability of a risk score for prediction of the long-term (8-year) benefit of the implantable cardioverter-defibrillator - Barsheshet, Alon; Moss, Arthur J; Huang, David T; McNitt, Scott; Zareba, Wojciech; Goldenberg, Ilan (Journal of the American College of Cardiology, 2012)
The present study was designed to explore the 8-year survival benefit of a nonresynchronization implantable cardioverter-defibrillator (ICD) according to a simple risk stratification score. There is limited information regarding factors that predict the benefit of primary prevention with an ICD during long-term follow-up. This study used a previously developed risk score including 5 clinical factors (New York Heart Association functional class >II, age >70 years, blood urea nitrogen >26 mg/dl, QRS duration >0.12 s, and atrial fibrillation) to evaluate 8-year ICD survival benefit within risk score categories among 1,191 MADIT-II (Multicenter Automatic Defibrillator Implantation Trial II) patients. Patients with low (0 risk factors, n = 345) and intermediate risk (1 to 2 risk factors, n = 646) demonstrated a significantly higher probability of survival at 8-year follow-up when treated by ICD as compared with non-ICD therapy (75% vs. 58%, p = 0.004; and 47% vs. 31%, p < 0.001, respectively). By contrast, among high-risk patients (3 or more risk factors, n = 200), there was no significant difference in 8-year survival between the ICD and non-ICD subgroups (19% vs. 17%, p = 0.50). Consistently, multivariate analysis showed that ICD therapy was associated with a significant long-term survival benefit among low- and intermediate-risk patients (hazard ratio [HR]: 0.52, p < 0.001, and HR: 0.66, p < 0.001, respectively), whereas treatment with an ICD was not associated with a significant benefit among high-risk patients (HR: 0.84, p = 0.25). These findings suggest that a simple risk score can identify patients who derive significant long-term benefit from primary ICD therapy. High-risk patients with multiple comorbidities composed 17% of the MADIT-II population and did not derive long-term benefit from nonresynchronization device therapy.